2017
DOI: 10.1111/jhn.12445
|View full text |Cite
|
Sign up to set email alerts
|

A novel processed food classification system applied to Australian food composition databases

Abstract: This Australian processed food classification system will allow researchers to easily quantify the contribution of processed foods within the Australian food supply to assist in assessing the nutritional quality of the dietary intake of population groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
(51 reference statements)
1
21
0
Order By: Relevance
“…Over half of the SOBF present were classified as nutrient-poor UPF. This is consistent with other studies that have found a large proportion of such highly processed foods present in the Australian food supply [ 74 , 75 ]. In fact, most new products launched in Australia in 2015 were UPF [ 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…Over half of the SOBF present were classified as nutrient-poor UPF. This is consistent with other studies that have found a large proportion of such highly processed foods present in the Australian food supply [ 74 , 75 ]. In fact, most new products launched in Australia in 2015 were UPF [ 76 ].…”
Section: Discussionsupporting
confidence: 93%
“…Difficulties with classification are not unique to our study; other authors have recognized that the broad NOVA definitions require some interpretation by researchers [29], which means that foods are not always uniformly categorized among different studies [30]. In Australia, thousands of foods within the Australian national food composition database AUSNUT have been categorized according to the NOVA classification [31], thus enabling consistent classification between researchers in that country. However, it is not always possible to determine the brand of food analysed in that database, or to know how similar, or different, Australian food stuffs are in comparison to those from New Zealand.…”
Section: Discussionmentioning
confidence: 99%
“…Ultra-processed food purchasing and consumption patterns have been described in several countries [4], with studies in Brazil [17, 32-35], Chile [16, 36], Colombia [37], Indonesia [38], Kenya [39], multiple European countries [9, 40], France [41], Norway [42, 43], Sweden [44], Australia [45, 46], New Zealand [47], USA [19, 20, 48, 49], Canada [18, 50, 51], and the UK [15, 40, 52]. …”
Section: Introductionmentioning
confidence: 99%